2019
DOI: 10.1515/rebs-2019-0084
|View full text |Cite
|
Sign up to set email alerts
|

Macroprudential Policies and Economic Growth

Abstract: In this paper we assess the effectiveness of macroprudential policies in ensuring a sustainable contribution of the financial sector to economic growth. Our results sustain that macroprudential policies have beneficial effects on economic growth, expressed by the GDP per capita growth rate. Macroprudential policies, adopted to strengthen the resilience of the financial system and decrease the buildup of systemic risks, contribute to the economic growth by assuring a stable financial system, and, therefore, a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…Therefore, to tackle inequality among high-income earners, it is crucial to have policies and strategies in place that prioritize inclusive growth, ensuring that the benefits of economic development reach all segments of society, rather than focusing solely on GDP per capita as a measure of progress. Our results support the findings documented by Andries and Melnic [71].…”
Section: Regions (S) Pedroni Tests For Cointegrationsupporting
confidence: 94%
“…Therefore, to tackle inequality among high-income earners, it is crucial to have policies and strategies in place that prioritize inclusive growth, ensuring that the benefits of economic development reach all segments of society, rather than focusing solely on GDP per capita as a measure of progress. Our results support the findings documented by Andries and Melnic [71].…”
Section: Regions (S) Pedroni Tests For Cointegrationsupporting
confidence: 94%
“…The finding that macroprudential tightening can be pro-growth is intensely debated in the empirical literature. Against this backdrop, our result is consistent with the conclusions by Boar et al (2017) and by Andries and Melnic (2019), while contrasting with the findings by Belkhir et al (2020) and Madeira (2020). Yet, none of these studies assesses the effects of macroprudential policy on real economic activity from the global perspective, focusing on panel data.…”
Section: Baseline Resultssupporting
confidence: 74%
“…impact on real economic activity is neutral or even positive (Andries and Melnic 2019;Belkhir et al 2020;Boar et al 2017;Davis et al 2019;Kim and Mehrotra 2019;Madeira 2020;Richter et al 2019;Rojas et al 2020). In a cross-country framework, international spillovers of domestic macroprudential intervention should be measured properly, which would facilitate adequate policy coordination among involved countries (Kang et al 2017;Norring 2019).…”
mentioning
confidence: 99%
“…This section will provide a quick overview of the literature on the impact of macroprudential policy on economic growth. In the literature, a negative impact of macroprudential policy on economic growth has been evidenced (Boar et al 2017;Kim and Mehrotra 2017;Alin and Florentina 2019;Belkhir et al 2022), while few have shown the positive effects (Andries and Melnic 2019). Boar et al (2017) documented that macroprudential policies are detrimental to growth in a panel of 64 developing and developed countries using the GMM.…”
Section: The Empirical Analysis Of Macroprudential Policies and Econo...mentioning
confidence: 99%
“…Boar et al (2017) and Kim and Mehrotra (2017) were further supported by Belkhir et al (2022), who studied the same subject matter during the banking crises in a panel of 134 countries, covering the time span 2000-2017, using the Early Warning System model. A contradiction emerged following the study by Andries and Melnic (2019) in a panel of 61 countries over the period 2000-2015, using System-GMM. Their findings support the premise that macroprudential interventions are good for growth.…”
Section: The Empirical Analysis Of Macroprudential Policies and Econo...mentioning
confidence: 99%